Simultaneous calibration of probe parameters and location errors of rotary axes on multi-axis CNC machines by using a sphere. (January 2022) - Fang, Zixi; Chen, Zezhong C.; Fang, Tao; Yi, Zhifu; Qi, Xietian
Research highlights: OMM systems calibration methods are influenced by machine geometric error. Automatic and simultaneous calibration of OMM systems and CNC machines are proposed. Special probing patterns are designed for calibrating the OMM systems and the machine. Uncertainty analysis shows the method is robust. Abstract: On-machine measurement (OMM) systems with touch-triggered probes are efficacious in productivity improvement. Machine motion errors impose major limitations on their accuracy for any OMM systems, especially when rotary axes motions are involved. This research proposes a precise measurement method to address this problem by simultaneously identifying the probe parameters and the location errors of rotary axes, using a touch-triggered probe to sample a sphere. This method is suitable for both periodic machine checks and OMM system recalibrations. The method formulates a mathematical model based on machine kinematics to represent errors between the theoretical probed data and the actual recorded data, minimizing which can solve for necessary parameters. Two proposed probing patterns simplify the solution to the model. Experiment results demonstrate that the method is effective and accurate. Monte Carlo simulations were carried out to prove the robustness of the method.